Current state of calcium silicate cements in restorative dentistry: a review - Camila Corral-Núñez; Eduardo Fernández-Godoy; Javier Martín Casielles; Juan Estay; Cristian Bersezio-Miranda; Patricia Cisternas-Pinto; Osmir Batista Batista-de Oliveira (Universidad de Antioquia, 2016)
Calcium silicate cements have been used as dental materials for more than twenty years; however, their use in restorative dentistry is more recent. Better mechanical properties and shorter curing times make them suitable for a variety of applications in which they are used as a substitute of dentin, including direct/indirect pulp capping and as cavity base/liner. These materials may also be used to restore enamel temporarily. This article seeks to review the available scientific evidence with a focus on their applications in restorative dentistry. The information was gathered by reviewing original scientific research articles and literature reviews published in journals available in databases such as Medline/Pubmed and Scielo, along with technical information provided by the manufacturers of these cements. This article describes the composition, instructions for use, and curing reaction of calcium silicate cements, as well as the scientific evidence on their applications in restorative dentistry.